Metabolic fingerprinting of must obtained from sun-dried grapes of two indigenous Cypriot cultivars destined for the production of ‘Commandaria’: A protected destignation of origin product - Constantinou, Savvas; Gómez-Caravaca, Ana; Goulas, Vlasios; Segura-Carretero, Antonio; Manganaris, George A. (My University, 2017)
Grapes's sun-dried process is one of the most critical steps in the production of 'Commandaria', a dessert wine product that is exclusively produced in Cyprus and derived from must obtained from two indigenous grape cultivars, namely 'Mavro' and 'Xynisteri'. Despite its significant economic importance, no data regarding the primary and secondary metabolites of the aforementioned cultivars exist. Thus, in the current study, the effect of sun drying process on the qualitative attributes and phenolic profile of 'Mavro' and 'Xynisteri' musts was dissected. Musts were analyzed at harvest and at the end of the sun-drying process that corresponds to ca. 30-40% water loss. Results highlighted significant differences in chemical composition of the must before and after the sun-drying process. Except for the increase of soluble solids content, a significant increment in glucose, fructose, total acidity, total phenols and total flavonoids contents was monitored. Subsequently, forty-two phenolic compounds were identified by LC-DAD-qTOE-MS revealing the polyphenolic fingerprint of the two cultivars. Results also indicated that changes in the phenolic composition of the obtained must are not only correlated with the dehydration effect, but both synthesis or degradation reactions occurred. In particular, the increases in the concentration of hydroxybenzoic acids were higher than the concentration effect for both cultivars. Regarding to hydroxycinnamates, dehydration caused a six-fold increase of hydroxycinnamic acid content in both cultivars. Intriguingly, the concentration of some hydroxycinnamic acids such as caffeic acid dihexoside and fertaric acid isomer went descending. Although the degradation of the internal side of the skin facilitate improved extractability from the skins to the grape pulp and therefore to the grape must, the sun-drying process may also induced stilbene and lignans synthesis production. A significant effect of dehydration on the postharvest biosynthesis of three groups of flavonoids (flavonols, flavan-3-ols, flavanonols), was also observed. This study sheds some light in the substantial changes that occur in specific metabolites during the sun drying process; such metabolites can be considered as potential factors that may determine organoleptic characteristics and biological properties of the end-product.
Keywords: Vitis vinifera; Autochthonous cultivars; Phenolic compounds; Sun-drying; Dessert wine; LC-DAD-qTOE-MS